Atlas of Asian Rhinoplasty - SUH, Man Koon (Springer Singapore, 2018)
This superbly illustrated atlas, featuring approximately 2,500 high-quality illustrations, will help all surgeons who perform rhinoplasty in Asian patients to achieve excellent aesthetic and functional outcomes. The differences in nasal anatomy and aesthetic goals between Asian and Western individuals are clearly explained, and the surgical materials appropriate to Asian rhinoplasty are identified. The full set of techniques employed in Asian rhinoplasty are then described and illustrated step by step, taking into account the important advances achieved in recent years. Among the procedures covered are dorsal augmentation using implants and autogenous tissue, tip plasty, tip reduction surgery, short nose correction, humpectomy, correction of alar-columellar disproportion, nostril and alar base reduction, and deviated nose correction. Guidance is offered on management of potential complications, and secondary rhinoplasty is also discussed. This book will enable surgeons to enhance the appearance of the nose in a way that is fully consistent with the other facial features of Asians.